Spontaneous pneumothorax. Review of clinical cases - Armand Ugon, Gustavo; Arévalo, Carlitos; Delbene, Roberto; Delbene, Roberto (Cirugía del Uruguay, 2006)
The pneumothorax as a pathology has been known for centuries. Spontaneous pneumothorax can be divided into primary and secondary. Our objective was to analyze spontaneous pneumothorax as the pathology which leads the patient to consult the Emergency Service of Pasteur Hospital, its distribution by sex and age, size, topography, time of the year in which it appears, signs of this symptomatology on hospitalization, its treatment and evolution as well as to compare the results with international data